Job Safety Analysis (Jsa) Sebagai Upaya Pengendalian RisikoKecelakaan Kerja Pada Pekerjaan Pengecoran LogamDi Pt Aneka Adhilogam Karya Ceper Klaten - SOLANDA, SOLANDA; , Tarwaka, PGDip., Sc., M.Erg; , Dwi Astuti, SKM., M.Kes (2016)
Job safety analysis or JSA is a technique to identify a job so that every type of work to do the appropriate precautions based on the type of work performed. In the foundry company are extremely high levels of occupational hazards that cause of work accident. So that a job safety analysis or JSA. So that a job safety analysis or JSA. This study aims to determine Job Safety Analysis (JSA) as an effort to control the risk of of work accident on the job at the foundry Karya PT Aneka Adhilogam Ceper Klaten.. Type of research is analytic descriptive research with the total sample of 43 samples obtained by using the exhaustive sampling. The result showed that it of work induction and casting/molding including the extremely high level of risk that can lead to accidents caused by work. It can be concluded Job Safety Analysis (JSA) can be used as an effort to control the risk of work accident in metal foundry work. The Company needed to make priorities and risk control in accordance with the use of alternative risk contro lthat is engineering, administrative controls and APD.